Distance learning technologies at the National University of Pharmacy - Kotvitska , A.; Galiy, L.; Krutshikh, T. (New Collegium, 2020)
The article is devoted to the introduction of distance learning technologies at the National University of Pharmacy. This direction was started more than 10 years ago, tested on applicants for higher education of full-time and part-time education, as well as among pharmacists-interns of the Institute for Advanced Training of Pharmacy Specialists of NUPh. Accumulated application experience of distance technologies was used successfully during the education of applicants for higher education in the period of quarantine.